A New Fault Detection and Classification Scheme in MTDC Grids with Hybrid Cable and Overhead Transmission Line - Zahra Moravej; Amir Imani; Mohammad Pazoki (مجله مدل سازی در مهندسی)
The growth of exploitation of distributed generation sources (DGs) such as offshore wind farms makes DC networks an interesting alternative to conventional AC grids. But protection of DC lines is one of the main challenges of these grids especially in hybrid non-homogenous corridors including underground cables and overhead lines. In this paper, a new single-end time domain-based protection scheme for fault detection and classification is presented with remarkable features such as easy implementation, low computation burden, low sampling frequency, no setting parameters requirement, and also appropriate performance in noisy conditions. To validate the proper performance of the proposed scheme, several scenarios are simulated including internal and external DC and AC faults, and severe load variations in EMTDC/PSCAD software environment. Also, some hybrid line scenarios such as line length variation, OHL or Cable length changes, and increasing the number of line segments are investigated. The result shows desirable performance in various conditions.